Effectiveness of reminiscence therapy in older people residing in residential structures: a pilot study with a quasi-experimental design - Gil, I.; Bobrowicz-Campos, E.; Silva, R.; Cavaleiro, A. (Atas do VI Congresso de Investigação em Enfermagem Ibero-Americana e de Países de Língua Oficial Portuguesa, 2021)
Introduction: The specificities of advanced age are associated with a multidimensional decline, increasing the institutionalization of older people in residential structures. However, such structures are not always on par with older peoples’ needs, potentiating cognitive decline and depressive symptomatology, and impacting their quality of life (Harsányiová & Prokop, 2018). Among the therapeutic interventions that can be introduced in these structures, reminiscence therapy (RT) emerges in the literature as an intervention that values the person’s human dimension and life trajectory (Peix, 2009). Objectives: This study aims to analyze the effectiveness of a group RT program (composed by the main component and a maintenance component) on the cognition, depressive symptomatology and quality of life of older people residing in residential structures. Methodology: A quasi-experimental study was carried out, implementing an RT program for 14 weeks in residential structures. As eligibility criteria, older persons were included if they were 65 years or more of age, had the ability to remain in a group and participate in the program’s activities, and did not have severe cognitive decline. The relevant clinical outcomes were assessed in three moments using the Montreal Cognitive Assessment scale, the 10-items Geriatric Depression Scale, and the World Health Organization Quality of Life scale - module for older adults (short version). Results: Of the 50 older people included in the initial assessment (32 women and 18 men, with an average age of 83.32 ± 7.76 years, and an average education of 5.48 ± 4.05 years), 35 (mean age of 84.17 ± 7.46 years, average education of 6.14 ± 4.49 years) completed the main component. Of these, 28 (average age of 84.25 ± 7.66 years, average education of 6.18 ± 4.57 years) completed the maintenance component. Overall, after delivering the program’s main component, there was stabilization in the older persons cognitive performance, with marginally significant improvements in the domain of attention, visuospatial and executive functions. In the final assessment, after the maintenance component of the RT program was carried out, statistically significant improvements were confirmed in the domain of deferred evocation. Although there were no statistically significant changes in older persons’ depressive symptomatology and quality of life, 50% of the participants who completed both components increased their overall quality of life scores. Conclusions: Although statistically significant improvements in older peoples’ overall cognitive function, depressive symptomatology and quality of life were not confirmed, the results of this study demonstrate the potential of RT in stabilizing these outcomes from a clinical viewpoint, with improvements in some subdomains. Nonetheless, considering that some of the participants presented an early stage of cognitive decline, these results can be seen as a significant therapeutic effect. Given the lack of studies in Portugal focused on the effectiveness of group RT programs, this pilot study constitutes a starting point for future studies with more robust designs and larger samples.